With a Little Help from my Friends : the Multiplier Effect of Public Subsidies through Private Support (2017)
Conditional cash transfer (CCT) programs have become an important component of social assistance in developing countries. CCTs, as well as other cash subsidies, have been criticized for allegedly crowding out private transfers. Whether social programs crowd out private transfers is an important question with worrisome implications, as private support represents an important fraction of households? income and works as a risk sharing mechanism in developing countries. Furthermore, empirical evidence on the effect of public transfers on private transfers is mixed. This paper contributes to the literature by using a unique dataset from the quasi-experimental evaluation of a CCT in Colombia and an empirical strategy that allows us to correct for pre-existing differences between treated and control groups. Our results suggest that the public transfer did not crowd out private transfers, neither in the short-run nor in the middle-run. Instead, it increased the probability of receiving support in cash, in kind